The relationship between knowledge and community behavior in improving the immune system during the COVID-19 pandemic era in Barong Tongkok Village - Stevania Windi; Lucia Vita Inandha Dewi; Inaratul Rizkhy Hanifah (Jurnal Ilmiah Farmasi, 2023)
Abstract Background: Within 2 years of the COVID-19 pandemic, stopping the spread of COVID-19 in the community can be done with adequate knowledge about immune system improvement behaviors and the use of health supplements to improve the body's immune system.Objective: This study aims to determine the relationship between the level of knowledge and community behavior in improving the immune system in Barong Tongkok Village in the era of the COVID-19 pandemic.Method: This study is a quantitative type with a cross-sectional method conducted in Barong Tongkok Village with a total sample of 356 respondents from 4,787 total populations. Analysis of results is carried out with univariate tests to concentrate and display data, while bivariate tests are statistical analyses of chi-square tests to see the relationship between two variables.Results: A univariate analysis revealed that the level of knowledge in the high category was 55.6% and the behavior of improving the immune system in the good category was 50.8%. The results of the bivariate test analysis with the chi-square test revealed a significant relationship between the level of knowledge and the behavior of improving the immune system (p = 0.000).Conclusion: There is a relationship between the level of knowledge and the behavior of improving the immune system in Barong Tongkok Village.Keywords: Level of knowledge, behavior, immune system, COVID-19 pandemic Intisari Latar belakang: Dalam kurun waktu 2 tahun lamanya pandemi COVID-19 telah berlangsung, penghentian penyebaran COVID-19 di masyarakat bisa dilakukan dengan pengetahuan yang memadai tentang perilaku peningkatan sistem imun dan penggunaan suplemen kesehatan untuk memperbaiki sistem imun tubuh.Tujuan: Studi ini bertujuan untuk mengetahui hubungan antara tingkat pengetahuan, dengan perilaku masyarakat dalam peningkatan sistem imun di Kelurahan Barong Tongkok di era pandemi COVID-19. Metode: Penelitian ini termasuk jenis kuantitatif dengan metode cross-sectional dilakukan di Kelurahan Barong Tongkok dengan jumlah sampel 356 responden dari 4.787 populasi masyarakat, analisis hasil dilakukan dengan uji univariat untuk mempersentasekan dan menampilkan data, sedangkan uji bivariat yaitu analisis statistika uji chi-square untuk melihat hubungan antara dua variabel.Hasil: Analisis univariat diperoleh bahwa tingkat pengetahuan dengan kategori tinggi sebesar 55,6%, dan perilaku peningkatan sistem imun dengan kategori baik sebesar 50,8%. Hasil analisis uji bivariat dengan uji chi-square diperoleh hubungan yang signifikan antara tingkat pengetahuan dengan perilaku peningkatan sistem imun (p=0,000).Kesimpulan: Terdapat hubungan antara tingkat pengetahuan dengan perilaku peningkatan sistem imun di Kelurahan Barong Tongkok.Kata kunci: Tingkat pengetahuan, perilaku, sistem imun, pandemi COVID-19